2021
DOI: 10.1080/24748668.2021.1936408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of corner kicks at the FIFA Women’s World Cup 2019 in relation to match status and team quality

Abstract: This study analysed the characteristics of 476 corner kicks taken during 52 matches at the FIFA women's World Cup 2019. The effect of current match status/team quality was examined, and the corner characteristics associated with the 17 goals scored from corners (3.6%) and 93 shots on-target (19.5%) were identified. Goals from corners were more likely from dynamic attacks or with 1-4 defenders for short corners. Shots on-target were more likely from corners delivered into GA3&CA3 and the outer zones, ≥6 attacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
7
2
1
Order By: Relevance
“…Contrastingly, open trajectories (or outswing) were most frequent in other European leagues (Spanish, Portuguese, Italian, German, and French), especially for indirect corners [19]. Some studies [16,17,42] reported that professional teams use more outswing trajectories and bottom level inswing, which is contrary to our results. Caution must be taken when comparing this data with amateur players with studies performed with top level players.…”
Section: Delivery Typecontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrastingly, open trajectories (or outswing) were most frequent in other European leagues (Spanish, Portuguese, Italian, German, and French), especially for indirect corners [19]. Some studies [16,17,42] reported that professional teams use more outswing trajectories and bottom level inswing, which is contrary to our results. Caution must be taken when comparing this data with amateur players with studies performed with top level players.…”
Section: Delivery Typecontrasting
confidence: 99%
“…In our study, 31% of the 500 corners resulted in attempts at goal, with 6% of these resulting in a goal. This is slightly higher than previous studies, which range from 2.2% to 3.6% [13,[16][17][18]21,22,41]. Successful teams were more clinical in front of goal, scoring 8% of their corners, with unsuccessful teams scoring 4%.…”
Section: Player Of the First Touch And Outcomecontrasting
confidence: 56%
See 2 more Smart Citations
“…Os próprios autores calcularam a confiabilidade intra e inter-observador na sua amostra, sanando assim a ausência de tal evidência científica na literatura. Muitos pesquisadores têm optado por esse método para que assim apresentem as evidências de validade da sua ferramenta de coleta, visto que os valores de confiabilidade e validade da fermenta são muito importantes para que se possa analisar o quão confiável são seus resultados Iván Baragno et al, 2021;Lee & Mills, 2021).…”
Section: Breve Comparação Com As Tecnologias Utilizadas No Futebol Ma...unclassified